A Quasi-Experimental Study on the Development of Creative Writing Skills in Primary School Students - Marta-Iuliana Vicol; Monalisa-Laura Gavriluț; Liliana Mâță (MDPI AG, 2024)
The purpose of this research was to evaluate the impact of using an educational program on the development of creative writing skills in fourth-grade students. Creative writing is an important component of teaching, learning, and assessment at the level of primary education. The objectives of the study aimed to identify the general level of development of creative writing skills and establish any significant differences in the development of specific components of creative writing skills (narrative voice, characterization, mood and atmosphere, language and technical aspects of writing, dialogue, narration, setting, image and plot). A quasi-experimental design with intervention and control groups was used. A total of 146 students from 3 public school institutions in the city of Bacau, Romania, that include elementary grades participated in the study. The research group consisted of 73 students in the intervention group and 73 students in the control group. A paired-samples t test was used to compare the scores for two paired variables. The research results have shown that creative writing skills are developing in young school-age students. Also, it was found that there are significant differences in the students from the experimental group, compared to the students in the control group, at the level of the nine components of creative writing skills.